Novel sound absorption materials produced from air laid non-woven feather fibres. Issue 9 (September 2018) - Dieckmann, Elena; Dance, Stephen; Sheldrick, Leila; Cheeseman, Christopher
Abstract: This research has investigated the use of feather fibres to produce sound absorption materials as an alternative to the oil derived synthetic plastics that currently dominate the sound absorption materials market. In this paper we show that clean and disinfected waste feathers from the poultry industry can be processed into fibres and air laid using commercial pilot plant facilities to form non-woven feather fibre composite mats. By varying the composition and processing conditions, materials with a range of different properties such as thickness and density were produced. The sound absorption coefficients of samples was determined using the impedance tube method (BS EN ISO 10534-2: 1998), using normal incidence sound between 80 and 1, 600 Hz. The data reported shows that air laid non-woven feather fibre mats have improved sound absorption coefficients compared to other natural materials used for sound absorption for a given thickness, particularly in the problematic low frequency range between 250 to 800 Hz. We conclude that air laid non-woven feather fibres have high potential to be used as effective and sustainable sound absorption materials in aerospace, automotive, buildings, infrastructure and other applications where sound absorption is required.